The different role of mandatory access in German regulation of railroads and telecommunications - Günter Knieps (Albert-Ludwigs-Universität Freiburg, Institut für Verkehrswissenschaft und Regionalpolitik, 2006)
Network services can be provided efficiently in competitive markets, if nondiscriminatory access to the complementary infrastructure capacities is guaranteed. The sector-symmetric application of the disaggregated regulatory approach to railways and telecommunications reveals the different role of mandatory access. Whereas in telecommunications only the local loop may create a remaining regulatory problem, mandatory access has to be guaranteed with respect to the railway infrastructure as a whole. In spite of the large phasing-out potentials of sector-specific regulation in telecommunications, this sector is still under the burden of overregulation. In contrast, in the railway sector mandatory access has been introduced only recently.
Older version: http://hdl.handle.net/10419/23018
Keywords: 330